(untitled) (Journal of Education and Educational Development, 2020)
Developing countries have seen a direct influence of foreign players on their educational policies. This influence of foreign players on the Pakistani educational policy has been direct and prominent after 9/11 attacks. This paper looks into the effectiveness of money spent by the donor nations to malign the effect of Islamization in the Pakistani society. This research was conducted taking into consideration the ideas that investment in the Pakistani education sector by foreign donors have not westernized the Pakistani youth and that there is no difference between the perception of the Pakistani youth and their parents with regard to culture and religion. The sample selected consisted of 120 youngsters aged between 16 to 18 years of age. A questionnaire consisting of 17 yes/no questions was used to collect the required data. The results from the research showed that the family structure in Pakistan was half way between traditional and western. There were certain things that the Pakistani youth understood as an essential part of their lives, and there was no compromise on the traditional values, whereas there were other things that the youth considered less important and these were steadily disappearing from their set of traditional values.